Characteristics of spatial distribution for microbial ecology inside and outside source water reservoir. (15th August 2021) - Guo, Jun; Zheng, Yuanyuan; Teng, Jinhao; Wang, Xumin; Song, Jiaxiu
Abstract: Although the steady-state transition caused by ecological changes is well known, the microorganisms involved are rarely understood. Gradual microbial community changes induced by the storage and operation of reservoirs were investigated in this study. Microbial 16S rRNA (16S ribosomal RNA) and ITS (Internal Transcribed Spacer) genes were analyzed by high-throughput sequencing to explore the microbial diversity and interaction between microbial species and environmental factors inside and outside reservoirs. The results showed Chao parameters outside the reservoirs were significantly higher than those inside reservoirs, indicating that there are more species outside the reservoir. After the water enters the reservoir, α-, β-, γ-Proteobacteria decreased in abundance, but the species of Cyanobacteria, Verrucomicrobia and Planctomycete were enriched along with the water flow of the reservoirs. The rising trend of Cyanobacteria in the lower reaches of the reservoir proves the aggravation of eutrophication in the reservoir. Eukaryotic algae of high abundance were also found in the reservoir: Bacillariophyta (diatom), Chlorophyta (green algae), and Cryptomonadaceae . Less amount of these eukaryotic algae observed outside the reservoir further confirmed the eutrophication tendency inside the reservoir. Therefore, as the prolongation of residence time in the reservoir, the degree of eutrophication was enhanced accompanied by the directional transition of community structures. It was found that the decrease abundance of methylophilaceae (aerobic denitrification), pelagibacter and xylophilus (aerobic oxidation) occurred simultaneously with the increasing concentrations of CODMn, TOC and NO3 − -N after entering the reservoir. Actinobacteria was found to be the most dominant population. Some Fungi enriched in the reservoir such as Chytridiomycota, Sclerotiniaceae, and Rhizophydium are related to algae proliferations, which may increase the risk of forming water odor. The degree of decay in the reservoir is considered to be increasing due to rapid growth of both Bacteroidia and Chytridiomycota, which are supposed to be indicator bacteria for decaying. The detention area in the reservoir is likely to be an important driving factor. The research confirmed the influence factors of eutrophication and the ecological risk of the reservoir. The discovery of some functional microorganisms in the reservoir help understand the relationship between the ecological effect and the safety of drinking water source. Graphical abstract: Image 1 Highlights: Ecological function and negative effects for the reservoir were verified. The increasing of Actinobacteria and Fungi was related to the risk of water odor. Cyanobacteria and eukaryotic algae grow exponentially in the reservoir. The change of populations reduces the capacity of aerobic oxidation.